As to the subject and system of crimes against family, minors rights and interests - Гальцова, В. В. (Problems of legality, 2014)
The article studies the problem of subject of crime against family, rights and interests of minors. The author analyses the structure and content of family relations that secure rights and interests of minors. Basin on this it is suggested to single out the criminal responsibility for these crimes in an independent chapter of the Special Section of the Penal Code of Ukraine.